A five-week periodized carbohydrate diet does not improve maximal lactate steady-state exercise capacity and substrate oxidation in well-trained cyclists compared to a high-carbohydrate diet - Prieto-Bellver, G.; Diaz-Lara, J.; Bishop, D. J.; Fernández-Sáez, J.; Abián-Vicén, J.; San-Millan, I.; Santos-Concejero, J. (Nutrients, 2024)
There is a growing interest in studies involving carbohydrate (CHO) manipulation and subsequent adaptations to endurance training. This study aimed to analyze whether a periodized carbohydrate feeding strategy based on a daily training session has any advantages compared to a high-carbohydrate diet in well-trained cyclists. Seventeen trained cyclists (VO2peak = 70.8 ± 6.5 mL·kg-1·min-1) were divided into two groups, a periodized (PCHO) group and a high-carbohydrate (HCHO) group. Both groups performed the same training sessions for five weeks. In the PCHO group, 13 training sessions were performed with low carbohydrate availability. In the HCHO group, all sessions were completed following previous carbohydrate intake to ensure high pre-exercise glycogen levels. In both groups, there was an increase in the maximal lactate steady state (MLSS) (PCHO: 244.1 ± 29.9 W to 253.2 ± 28.4 W; p = 0.008; HCHO: 235.8 ± 21.4 W to 246.9 ± 16.7 W; p = 0.012) but not in the time to exhaustion at MLSS intensity. Both groups increased the percentage of muscle mass (PCHO: p = 0.021; HCHO: p = 0.042) and decreased the percent body fat (PCHO: p = 0.021; HCHO: p = 0.012). We found no differences in carbohydrate or lipid oxidation, heart rate, and post-exercise lactate concentration. Periodizing the CHO intake in well-trained cyclists during a 5-week intervention did not elicit superior results to an energy intake-matched high-carbohydrate diet in any of the measured outcomes.